2014
DOI: 10.1159/000358675
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Sensitizing Effect of LXR Agonist T0901317 in High-Fat Fed Rats is Associated with Restored Muscle GLUT4 Expression and Insulin-Stimulated AS160 Phosphorylation

Abstract: Background/Aim: Liver X receptors (LXRs) are ligand-activated transcription factors that were shown to stimulate hepatic lipogenesis leading to liver steatosis and hypertriglyceridemia. Despite their pro-lipogenic action, LXR activators normalize glycemia and improve insulin sensitivity in rodent models of type 2 diabetes. Antidiabetic action of LXR agonists is thought to result from suppression of hepatic gluconeogenesis. However, it remains unclear whether LXR activation affects muscle insulin sensitivity. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 26 publications
3
19
1
1
Order By: Relevance
“…The results show that the concentrations of serum ALT, AST, and ALP did not change in non-diabetic rats after CLP or treatment with insulin. Conversely, insulin completely rescued liver enzymes in all CLP diabetic animals, probably by affecting hepatic glucose levels and lipid metabolism [22][23][24]. Another explanation for the dysfunction of organs located away from the focus of infection may be inappropriate neutrophil activation, the accumulation of neutrophils within the microcirculation next to certain organs, and neutrophil migration to regions other than the primary focus [25]; however, liver neutrophil infiltration was not observed in our study.…”
Section: Cellular Physiology and Biochemistrycontrasting
confidence: 48%
“…The results show that the concentrations of serum ALT, AST, and ALP did not change in non-diabetic rats after CLP or treatment with insulin. Conversely, insulin completely rescued liver enzymes in all CLP diabetic animals, probably by affecting hepatic glucose levels and lipid metabolism [22][23][24]. Another explanation for the dysfunction of organs located away from the focus of infection may be inappropriate neutrophil activation, the accumulation of neutrophils within the microcirculation next to certain organs, and neutrophil migration to regions other than the primary focus [25]; however, liver neutrophil infiltration was not observed in our study.…”
Section: Cellular Physiology and Biochemistrycontrasting
confidence: 48%
“…The results showed that miR-499-5p negatively regulates AKT/GSK activation by targeting PTEN. It has been suggested that glucogenesis and lipogenesis are two major functions of livers [21]. In this study, we found that overexpression of miR-499-5p in NCTC cells significantly increased the glycogen content, while inhibition of miR-499-5p reduced the glycogen content.…”
Section: Discussionsupporting
confidence: 50%
“…Insulin stimulates hepatic lipogenesis by increasing the mRNA and the processed nuclear form of sterol regulatory element-binding protein-1c (SREBP-1c), a transcription factor that activates all the genes needed to produce fatty acids and triglycerides in liver [5]. Insulin-dependent SREBP-1c transcriptional regulation also requires liver X receptor (LXR) activation [6,7].…”
Section: Introductionmentioning
confidence: 99%